2020
DOI: 10.1021/acssuschemeng.0c06913
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Elaboration, Processing, and Derivatization of Cellulosic Materials Using Ionic Liquids

Abstract: Sustainable biopolymers are promising raw resources for the development of novel biomaterials with vast potential in various application fields. Nonetheless, the processing and derivatization of biomaterials is still a challenge due to the low solubility, especially of cellulose, in common solvents. Since the discovery that most biopolymers display significant solubility in ionic liquids (ILs), this method opened new routes for processing and derivatization of such compounds, thus allowing the access to novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 110 publications
0
35
0
Order By: Relevance
“…The hybrid cellulose/GO films, without an obvious interface between phases, display a maximum capacity of 109.1 mg/g for Ce 3+ adsorption [100]. However, the GO incorporation with cellulose in ionic liquids for water purification applications has been hampered by difficulties due to the small size of GO particles that are difficult to recover [100,101]. Fabrication of magnetic nanocellulose based adsorbents with the aim of magnetic separation and reuse is a viable approach; it allows processing large effluent volumes and adsorbent regeneration [102].…”
Section: Figurementioning
confidence: 99%
“…The hybrid cellulose/GO films, without an obvious interface between phases, display a maximum capacity of 109.1 mg/g for Ce 3+ adsorption [100]. However, the GO incorporation with cellulose in ionic liquids for water purification applications has been hampered by difficulties due to the small size of GO particles that are difficult to recover [100,101]. Fabrication of magnetic nanocellulose based adsorbents with the aim of magnetic separation and reuse is a viable approach; it allows processing large effluent volumes and adsorbent regeneration [102].…”
Section: Figurementioning
confidence: 99%
“…Cellulose, the most abundant polysaccharide material on Earth, has excellent physico–chemical properties, such as low cost, abundant availability, rich surface chemistry, biodegradability, biocompatibility, high thermal stability, good mechanical properties, and environmental benignity. These unique properties allow it to be used in a wide variety of applications in textile, packaging, paper, and lightweight composites [ 1 ]. Various cellulosic materials, such as nanoporous cellulose gel [ 18 ], cellulose microfibrils [ 19 ], and bacterial cellulose [ 20 ], were applied as an assistant medium, either as reductants or stabilizers of silver nanoparticles.…”
Section: Cellulose Formsmentioning
confidence: 99%
“…During the last few decades, polysaccharide-based materials have been considered as promising candidates in terms of abundance of supply and environmental viability. Moreover, their use in various fields has grown quickly [ 1 , 2 ]. Polysaccharides have influenced most modern technologies and can be easily seen in several applications.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] NC possesses an amphiphilic structure since different crystalline faces exposed have largely different polarity [25][26][27] as depicted in Figure 3. The polarity of the exposed crystal planes depends also on the cellulose polymorph considered: hydrophilic planes are the (100) for cellulose-I α , the (110) and (110) for cellulose-I β , and (110) for regenerated cellulose-II. On the other hand, the (220) planes of cellulose-I α and of regenerated cellulose-II, and the (200) planes of cellulose-I β are mostly hydrophobic.…”
Section: The Structure Of the Cellulosementioning
confidence: 99%
“…[11,52] The concept is that lipophilicity is not necessarily the opposite of hydrophilicity, but must be similarly quantified by a chemical potential difference of an appropriately chosen "lipophile". [53] Accordingly, proof of the NC amphiphilicity was provided by the diffraction patterns of cellulose crystals and by computational studies which suggested that water molecules and hydroxyl groups are on the (110) and (010) faces of the cellulose crystal, whereas the relatively nonpolar C-H groups are exposed on the (100) face, facilitating the formation of solvation "gaps" on that surface. [42] Upon drying, cellulose undergoes partly irreversible reorganization like aggregation or surface passivation to find the energetically most favorable state, a process named hornification.…”
Section: The Complex Role Of Hydroxyls: the Love-hate Relationship Between Nanocellulose And Watermentioning
confidence: 99%